(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Nutraceuticals, a broad category of food-derived products with possible health advantages, have attracted a lot of interest in the treatment of neurodegenerative diseases (NDDs), including multiple sclerosis, Parkinson’s disease, and Alzheimer’s disease. These disorders present considerable therapeutic challenges because of their complex etiology and limited treatment choices. They are characterized by progressive neuronal degeneration and related motor and cognitive impairments. Because of their capacity to alter different biochemical and molecular pathways linked to neurodegeneration, nutraceuticals play a crucial role in managing non-alcoholic fatty liver disease NDD. Important processes include control of protein aggregation, antioxidative stress, anti-inflammatory effects, and mitochondrial protection. Pre-clinical and clinical research have demonstrated the potential neuroprotective effects of compounds, such as omega-3 fatty acids, polyphenols (such as curcumin and resveratrol), and vitamins (such as Vitamin E and Vitamin D). Furthermore, as a supplementary strategy to traditional treatments, nutraceuticals have the ability to improve therapeutic results and halt the advancement of disease. Their accessibility, natural origin, and usually acceptable safety profile make them appealing candidates for long-term usage in the management of NDDs notwithstanding its potential, variables, including bioavailability, dose optimization, and response variability, pose challenges to the therapeutic use of nutraceuticals in NDDs. To create uniform dosages, clarify the mechanisms of action, and confirm their efficacy through well-planned clinical studies, more research is required.